# Solve for a 2a-9=(a+1)+13a+4

2a-9=(a+1)+13a+4
Since a is on the right side of the equation, switch the sides so it is on the left side of the equation.
(a+1)+13a+4=2a-9
Simplify (a+1)+13a+4.
14a+1+4=2a-9
14a+5=2a-9
14a+5=2a-9
Move all terms containing a to the left side of the equation.
Subtract 2a from both sides of the equation.
14a+5-2a=-9
Subtract 2a from 14a.
12a+5=-9
12a+5=-9
Move all terms not containing a to the right side of the equation.
Subtract 5 from both sides of the equation.
12a=-9-5
Subtract 5 from -9.
12a=-14
12a=-14
Divide each term by 12 and simplify.
Divide each term in 12a=-14 by 12.
12a12=-1412
Cancel the common factor of 12.
Cancel the common factor.
12a12=-1412
Divide a by 1.
a=-1412
a=-1412
Simplify -1412.
Cancel the common factor of -14 and 12.
Factor 2 out of -14.
a=2(-7)12
Cancel the common factors.
Factor 2 out of 12.
a=2⋅-72⋅6
Cancel the common factor.
a=2⋅-72⋅6
Rewrite the expression.
a=-76
a=-76
a=-76
Move the negative in front of the fraction.
a=-76
a=-76
a=-76
The result can be shown in multiple forms.
Exact Form:
a=-76
Decimal Form:
a=-1.16‾
Mixed Number Form:
a=-116
Solve for a 2a-9=(a+1)+13a+4

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top